Freshwater protists: unveiling the unexplored in a large floodplain system. (15th November 2021) - Metz, Sebastian; Huber, Paula; Accattatis, Victoria; Lopes dos Santos, Adriana; Bigeard, Estelle; Unrein, Fernando; Chambouvet, Aurélie; Not, Fabrice; Lara, Enrique; Devercelli, Melina
Summary: Protists play a fundamental role in all ecosystems, but we are still far from estimating the total diversity of many lineages, in particular in highly diverse environments, such as freshwater. Here, we survey the protist diversity of the Paraná River using metabarcoding, and we applied an approach that includes sequence similarity and phylogeny to evaluate the degree of genetic novelty of the protists' communities against the sequences described in the reference database PR 2 . We observed that 28% of the amplicon sequence variants were classified as novel according to their similarity with sequences from the reference database; most of them were related to heterotrophic groups traditionally overlooked in freshwater systems. This lack of knowledge extended to those groups within the green algae (Archaeplastida) that are well documented such as Mamiellophyceae, and also to the less studied Pedinophyceae, for which we found sequences representing novel deep‐branching clusters. Among the groups with potential novel protists, Bicosoecida (Stramenopiles) were the best represented, followed by Codosiga (Opisthokonta), and the Perkinsea (Alveolata). This illustrates the lack of knowledge on freshwater planktonic protists and also the need for isolation and/or cultivation of new organisms to better understand their role in ecosystem functioning.